Chia: a) ($x^{3}$ – $x^{2}$ -5x -3) : (x + 1) b) ($x^{3}$ – 7x + 6) : (x – 2) c) ($x^{3}$ + x$y^{2}$ – 2$y^{3}$) : (x – y)

Question

Chia:
a) ($x^{3}$ – $x^{2}$ -5x -3) : (x + 1)
b) ($x^{3}$ – 7x + 6) : (x – 2)
c) ($x^{3}$ + x$y^{2}$ – 2$y^{3}$) : (x – y)

in progress 0
Liliana 1 năm 2021-09-27T21:35:25+00:00 2 Answers 2 views 0

Answers ( )

    0
    2021-09-27T21:36:34+00:00

    ý a; = x^2-2x-3

    = ( x-3) .(x+1)

    ý b =x^2+2x-3

    =( x-1) .( x+3)

    ý c = 2y^2+xy -x^2

    Giải thích các bước giải:

    0
    2021-09-27T21:37:08+00:00

     `a; = x^2-2x-3`

    `= ( x-3) .(x+1)`

    `b =x^2+2x-3`

    `=( x-1) .( x+3)`

     `c = 2y^2+xy -x^2`

     

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )